ANALYSIS OF STUDENTS' UNDERSTANDING IN USING FORMAL AND INFORMAL EXPRESSION - Zulkifli Daud Akhmad; Nur Islan Amiri (Al-Lisan: Jurnal Bahasa, 2018)
Language is not only a tool of communication, furthermore language is an identity which describes the user of the language. Geoffrey Leech assumes that people must use certain expression depend on the situation. Therefore, the current research aims to analyze students’ understanding in using formal and informal expression. By conducting qualitative research then the researcher found that students’ difficulties in understanding formal and informal expressions is that students are accustomed in using phrases in informal form which made them tricky to recognize whether an expression is formal or informal. He also found that majority students thought that formal expressions were harder rather than informal expression to be learnt. Those difficulties were influenced by students’ basic skill of grammar, pronunciation and English vocabulary mastery.